Conspiracy Narratives and Religious Legitimation in Digital Politics: A Cross-Case Analysis of State-Linked Discoursesd the Success of Autocracy - Stefan Heep (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the relationship between conspiracy belief, religion, and the stability of authoritarian regimes by examining the structural similarities between religious modes of thinking and conspiracy belief in contemporary political contexts. The study departs from the growing use of conspiracy narratives by authoritarian state actors and the involvement of national religious actors and groups in supporting such narratives. The research adopts a qualitative approach and applies narrative analysis to ten conspiracy narratives disseminated by the governments of the United States, Russia, Israel, Turkey, and India through the internet and digital media. The findings show that conspiracy belief and religious belief share structural equivalence in their psychosocial functions, particularly in providing self-certainty, group affiliation, meaning orientation, and identity stabilization amid social complexity. However, conspiracy belief consistently operates as a defensive mechanism against threats to a narcissistic self-concept and perceived loss of control through the distortion of reality, whereas religious belief displays a broader and more context-dependent range of functions. The study also demonstrates that digital media and platform algorithms function as cognitive and emotional accelerators that intensify the reproduction of conspiracy narratives and the legitimation of authoritarian power. The implications of this research underscore the importance of critical approaches in the study of religion and politics, particularly for understanding how religion and conspiracy narratives operate as sources of power legitimation and regime stabilization in the digital public sphere. The originality of this study lies in its integration of political narrative analysis with perspectives from cognitive psychology and neuro- and biopsychological explanations within the study of religion and culture.